2015
DOI: 10.1515/znb-2015-0053
|View full text |Cite
|
Sign up to set email alerts
|

Novel conformationally constrained pyrazole derivatives as potential anti-cancer agents

Abstract: The synthesis of 17 novel conformationally constrained pyrazole derivatives is reported herein, along with the assessment of their anti-proliferative and antiangiogenic activities. The evaluation of their inhibitory effect on cell proliferation against HepG2, HeLa, and MCF-7 cells revealed the pyrrolo[2,3-g]indazole 23 as a potent inhibitor of cell growth with IC 50 values of 5 μm. Additionally, the inhibition of vascular endothelial growth factor by pyrazoles 20 and 23 (30 % and 35 %, respectively) in HeLa su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In a study concerning the cytostatic activity in cancer cell lines of novel conformationally rigid pyrazoles, Kasiotis et al synthesized two pyrazole-fused tetrahydroindol-4-ones [ 78 ]. Therefore, benzyl-protected tetrahydroindol-4-one 144 in the presence of lithium hexamethyldisilazane (LiHMDS) base under anhydrous conditions provided the corresponding enolate, which was subsequently condensed with 3-chlorobenzothiophene-2-carbonyl chloride or p -anisoyl chloride to afford the 1,3-diketone derivatives ( Scheme 27 ).…”
Section: Synthesis Of [45]-fused Polyheterocyclic Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study concerning the cytostatic activity in cancer cell lines of novel conformationally rigid pyrazoles, Kasiotis et al synthesized two pyrazole-fused tetrahydroindol-4-ones [ 78 ]. Therefore, benzyl-protected tetrahydroindol-4-one 144 in the presence of lithium hexamethyldisilazane (LiHMDS) base under anhydrous conditions provided the corresponding enolate, which was subsequently condensed with 3-chlorobenzothiophene-2-carbonyl chloride or p -anisoyl chloride to afford the 1,3-diketone derivatives ( Scheme 27 ).…”
Section: Synthesis Of [45]-fused Polyheterocyclic Structuresmentioning
confidence: 99%
“…Demethylation of 146 delivered diphenolic compound 147 in 85% yield. Evaluation of the cytostatic activity revealed that 147 had the most potent inhibitory activity against the growth of the panel of tested cancer cell lines [ 78 ].…”
Section: Synthesis Of [45]-fused Polyheterocyclic Structuresmentioning
confidence: 99%
“…Fused tricyclic pyrazole derivatives have been studied as necroptosis inhibitors [3,4], high affinity ligands for the human dopamine D4 receptor [5], phosphodiesterase 4 (PDE4) inhibitors [6], cannabinoid-2 receptor ligands [7], inhibitors of β-hematin formation conferring in vitro antimalarial activity [8] or inhibition of isocitrate dehydrogenase 1 (IDH1) [9]. Moreover, the tricyclic pyrazole core is present in compounds with antimicrobial [10,11,12] and antiproliferative activity [13,14,15]. The most widely used synthetic approach towards these compounds involves the reaction of α,β-unsaturated ketones and hydrazines [6,8,10,11,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, a Lewis acid promoted reaction of cycloalkanones with hydrazones has also been described to synthesize 2,3-diaryl-4,5,6,7-tetrahydro-1 H -indazoles [16]. It should be highlighted that these fused tricyclic pyrazole derivatives are characterized by their conformational restriction [15].…”
Section: Introductionmentioning
confidence: 99%